2013
DOI: 10.1038/ncomms2763
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of myosin II during Drosophila imaginal disc metamorphosis

Abstract: The motor protein non-muscle myosin II is a major driver of the movements that sculpt three dimensional organs from two dimensional epithelia. The machinery of morphogenesis is well established but the logic of its control remains unclear in complex organs. Here we use live imaging and ex vivo culture to report a dual role of myosin II in regulating the development of the Drosophila wing. First, myosin II drives the contraction of a ring of cells that surround the squamous peripodial epithelium, providing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 41 publications
0
49
0
Order By: Relevance
“…Previous research has shown apically localized Sqh to be involved in apical constriction, invagination and MyoII-dependent regulation of tension in epithelia (Aldaz et al, 2013; Monier et al, 2015; Zimmerman et al, 2010). We therefore examined whether knocking down sqh via RNAi may reduce cell survival or promote basal extrusion.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research has shown apically localized Sqh to be involved in apical constriction, invagination and MyoII-dependent regulation of tension in epithelia (Aldaz et al, 2013; Monier et al, 2015; Zimmerman et al, 2010). We therefore examined whether knocking down sqh via RNAi may reduce cell survival or promote basal extrusion.…”
Section: Resultsmentioning
confidence: 98%
“…6H) and miR-8 mutants also exhibit increased Ena (Loya et al, 2009). These proteins are involved in cortical F-actin bundling, F-actin polymerization and nucleation at adherens junctions and actomyosin contraction - molecular functions consistent with alterations in cell migration, cell-cell junction remodeling and cytokinesis, which may contribute to the G2 arrest of miR-8 expressing cells (Aldaz et al, 2013; Founounou et al, 2013; Geisbrecht and Montell, 2002; Koch et al, 2012; Lin et al, 2007; Mavrakis et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…Finally, the RLC-AE mutant had the most severe defect in the ATP hydrolysis rate and correspondingly had the most significant defect in constriction rate and tissue folding. Past work has suggested that RLC-EE can promote contraction (Aldaz et al, 2013; Escudero et al, 2007; Kasza et al, 2014). However, this result is only obtained when the RLC-EE is expressed in a background where wild-type RLC-TS is also present.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of cell size and shape is known to be driven by integrins under the control of the Ras‐signaling cascade for changes in cell shape (Domínguez‐Giménez et al, ), whereas patterns of oriented cell intercalation could be regulated by the Ft‐Ds‐Fj system as it is the case in the thorax (Bosveld et al, ) or by the Zipper, Sqh and RhoA proteins, as is the case in the embryo (Bertet et al, ). Intercalation could also be driven by external forces coming from myosin II activity in the peripodal membrane or from the hydraulic pressure of pumped hemolymph (Taylor & Adler, ; Aldaz et al, ). Note that the peripodial epithelium is also necessary to perforate the larval epidermis and it presumably contracts to allow the exit of the notum and of the wing blade through the larval epidermis (Fristrom & Fristrom, ; Pastor‐Pareja et al, ) (Fig.…”
Section: Morphological Variation Generated During Developmentmentioning
confidence: 99%